Knowledge, Attitude, and Practice of Health Care Professionals Toward Breastfeeding - Mohamed Kabouka; Ibtisam Hadeed; Soad Elmadah; Amal Said; Mohamed Hwiade; Suliman Abusrewil (AlQalam Journal of Medical and Applied Sciences, 2024)
Successful initiation and continuation of breastfeeding is proportionate to the attitude and knowledge of health care professionals toward breastfeeding; therefore, we conducted a study in Alkhoms district hospital, aimed to evaluate knowledge, attitude and practices of health care professionals toward breastfeeding. A well-structured questionnaire was designed to test their knowledge on Breastfeeding process, and their ability to deal with different problems and questions that may face during their practice. A total of 155 health care providers participates in this study [72 nurses, 25 midwives, and 58 junior doctors], all of them filled the questionnaire completely and each separately. The study has shown clearly deficiencies of health care providers in some aspects of their knowledge on and their abilities to deal with practical problems that may facing the lactating mother. إن البدء الناجح في الرضاعة الطبيعية ومواصلتها يتناسب مع موقف ومعرفة المتخصصين في الرعاية الصحية تجاه الرضاعة الطبيعية؛ لذلك، أجرينا دراسة في مستشفى منطقة الخوم، بهدف تقييم معرفة وموقف وممارسات المتخصصين في الرعاية الصحية تجاه الرضاعة الطبيعية. تم تصميم استبيان جيد البنية لاختبار معرفتهم بعملية الرضاعة الطبيعية، وقدرتهم على التعامل مع المشاكل والأسئلة المختلفة التي قد يواجهونها أثناء ممارستهم. شارك في هذه الدراسة ما مجموعه 155 من مقدمي الرعاية الصحية [72 ممرضة و25 قابلة و58 طبيبًا مبتدئًا]، وقد ملأ جميعهم الاستبيان بالكامل وكل على حدة. أظهرت الدراسة بوضوح أوجه قصور لدى مقدمي الرعاية الصحية في بعض جوانب معرفتهم وقدراتهم على التعامل مع المشاكل العملية التي قد تواجه الأم المرضعة